Pengaruh Attitude Towards Entrepreneurship terhadap Enterpreneurship Intention dengan Enterpreneurship Learning sebagai Moderasi pada Mahasiswa Jurusan Manajemen di IPB Internasional Bali - Anbarini, Ratih; Sitepu , Rismawati; Sarwoko, Endi; Darsana , Made (Jurnal Riset Pendidikan Ekonomi, 2025)
This study aims to analyze the effect of attitude on entrepreneurial intention moderated by entrepreneurship learning in management students at IPB Internasional Bali. Using a quantitative approach with a survey design, data were collected from 100 fourth semester students and above through questionnaires and analyzed using the SEM-PLS technique. The results showed that attitude has a significant effect on entrepreneurial intention with an R-Square value of 0.871, but entrepreneurship learning does not significantly moderate the relationship (p-value = 0.491). These findings provide insight into the importance of attitude in shaping entrepreneurial intention and the role of entrepreneurship learning in the context of higher education at IPB Internasional Bali.